Effect of Flap and Flapless Implant Surgical Techniques on Soft and Hard Tissue Profile in Single-Stage Dental Implants - Deepa Anumala; Modem Haritha; Sistla Sailaja; Egatela Prasuna; Gujjula Sravanthi; Nagireddy Ravindra Reddy (Wolters Kluwer Medknow Publications, 2019)
Introduction: Over the past 30 years, flap designs for implant surgery have been modified and atraumatic technique was introduced. It has several potential advantages, including reduction of complications at the patient level. The aim of the present study to compare the soft tissue profile and heights of crestal bone levels around the single-stage implants after single-piece implant placement with two different surgical techniques, that is, open flap procedure and flapless (FL) procedure. Materials and Methods: Thirty participants were randomly selected and categorized into two groups. Group 1 (flap technique) and Group 2 (flapless technique) consisted of 15 participants each. All of these participants underwent evaluation of soft tissue parameters of papillary index, probing pocket depth, sulcus bleeding index, and hard tissue evaluation such as crestal bone levels by radiovisiography at 0, 3, and 6 months. Results: All clinical parameters improved in FL technique when compared with the flap technique. Conclusion: The results concluded that the FL implant surgery results in lesser loss of interproximal bone and also results in better soft tissue changes when compared with the flap technique. However, controlled, further studies are needed to confirm this possibility.